LINGUISTIC PECULIARITIES OF HUMBLEBRAGGING AND OUTRIGHT BRAGGING IN PRE-ELECTION DEBATES - Topuria, Kristina (International Journal of Innovative Technologies in Social Science, 2023)
The article is devoted to the study of the phenomenon of bragging in general and its two main types: Humblebragging and Outright bragging in pre-election debates. Also, fundamental driver of the article is to reveal what linguistic “tricks” are employed by political actors when advertising themselves in order the audience to think highly of them. Theoretical material of the research is collected from the works of Peggy Klaus, Meredith Fineman, Ovul Sezer et la and Henry Alford. As for the practical material, it is mainly retrieved from American cable and satellite television network, C-Span. Based on above named sources, investigation revealed that various types of linguistic techniques such as: repetition, personal pronouns, idiomatic expressions, adjectives, intensifiers, comparative forms, superlative forms, rhetorical questions, rhetorical device such as enumeration etc, are used on frequent basis by politicians involved in political battle and bragging assuredly is very effective tool to knock your opponent down.